Paternal inheritance of chloroplast and mitochondrial DNA in the Huon pine (Lagarostrobos franklinii) - Birgit Kersten; Rob C. Kruijt; Avi Shmida; Tom J. de Jong (Tree Genetics & Genomes, 2026)
In conifers, plastid DNA is inherited through the male lineage via the pollen grain. By contrast, mitochondrial DNA is maternally inherited in the well-studied Pinaceae, but is often paternally inherited in other conifer families. This paper examines the mode of inheritance of plastids and mitochondria in the rare Tasmanian podocarp Lagarostrobos franklinii. It is the first molecular genetic study of organelle inheritance in the Podocarpaceae family. Two intraspecific crosses were established with the same iconic father, which was cloned from a tree from a uniform clonal stand, estimated to be 11,000 years old. Genome skimming and subsequent bioinformatic analysis identified polymorphic positions in the parental genomes of one cross. Our Illumina reads were aligned to a published plastome and to newly assembled DNA contigs that represent the partial mitogenome of the father. We used PCR-based markers derived from these polymorphisms to genotype parents and offspring of both crosses. Both plastid DNA and mitochondrial DNA were paternally inherited in all five offspring examined . This study provides new insights into patterns of organelle inheritance in conifers and the evolution of this trait.

DNA markers targeting three cellular genomes for the discrimination between Taxus baccata, T. cuspidata and their hybrid - Daniel Bross; Hilke Schroeder; Emilia Pers-Kamczyc; Birgit Kersten (Tree Genetics & Genomes, 2025)
The species identification in Taxus based on morphological differences has historically been difficult, and molecular markers are important tools to consistently identify Taxus species. The increasing availability of public DNA sequencing data supports efforts to develop such markers. In this study, a new molecular PCR-based marker for the differentiation of the three most abundantly occurring Taxus species in Europe, T. baccata , T. cuspidata , and their cultivated hybrid, T. × media , was identified in the ITS region in the nuclear genome, as well as markers for the identification of T. baccata and T. cuspidata that were identified in the psbB_psaI intergenic linker and chlN region of the chloroplast genome and in the cox1 region of the mitochondrial genome. Markers identified in public data were validated with 106 T. baccata , 12 T. × media and 10 T. cuspidata individuals with pre-existing phenotypical species declarations. The marker test results matched the identity of all but seven samples, and all deviating samples were identified by the markers as T. × media . In combination, these markers can also identify the crossing direction of T. × media samples. The results of the tests on T. × media samples in this study support a paternal inheritance of the mitochondrial genome in T. × media and revealed the crossing direction of multiple cultivars for which it was previously unknown. A minimal marker set was defined for rapid and cost-efficient identification of the analysed Taxus species and the crossing direction in T. × media .

Patterns of Adaptation to Drought in Quercus robur Populations in Central European Temperate Forests - Tetyana Nosenko; Hilke Schroeder; Ina Zimmer; Franz Buegger; Franziska Orgel; Imke Burau; Prasath Balaji Sivaprakasam Padmanaban; Andrea Ghirardo; Ronja Bracker; Birgit Kersten; Jörg‐Peter Schnitzler (Global Change Biology, 2025)
In order to predict the future of European forests, it is crucial to assess the potential of the dominant perennial species to adapt to rapid climate change. The aim of this study was to reconstruct the pattern of distribution of drought tolerance in Quercus robur in the current center of the species' range. The distribution and plasticity of drought‐related traits in German populations of Q. robur were assessed and the effects of spring phenology and species demographic history on this distribution were evaluated using a drought stress experiment in a common garden. We show that variation of drought‐related functional traits, including intrinsic water use efficiency (iWUE), leaf osmotic potential (π), and rate of drought‐induced defoliation, is high within Q. robur populations. However, frequency of trees with high estimated constitutive drought tolerance increases with decreasing water availability in the regions of population origin, indicating local adaptation to drought. A strong correlation between the distribution of drought‐related traits and spring phenology observed in Q. robur suggests that adaptation to water deficit interacts with adaptation to the strong seasonality of the central European climate. The two processes are not influenced by the history of post‐glacial recolonisation of central Europe. The results of this study provide a basis for optimistic prognoses for the future of this species in the center of its current distribution range.

Identification of full-sibling families from natural single-tree ash progenies based on SSR markers and genome-wide SNPs - Melina Krautwurst; Franziska Past; Birgit Kersten; Ben Bubner; Niels A. Müller (Journal of Plant Diseases and Protection, 2024)
Common ash, Fraxinus excelsior , is threatened by the invasive pathogen Hymenoscyphus fraxineus , which causes ash dieback. The pathogen is rapidly spreading throughout Europe with severe ecological and economic consequences. Multiple studies have presented evidence for the existence of a small fraction of genotypes with low susceptibility. Such genotypes can be targets for natural and artificial selection to conserve F. excelsior and associated ecosystems. To resolve the genetic architecture of variation in susceptibility it is necessary to analyze segregating populations. Here we employed about 1000 individuals of each of four single-tree progenies from potentially tolerant mother trees to identify full-sibling (full-sib) families. To this end, we first genotyped all 4000 individuals and the four mothers with eight SSR markers. We then used the program COLONY to predict full-sibs without knowledge of the paternal genotypes. For each single-tree progeny, COLONY predicted dozens of full-sib families, ranging from 3–166 individuals. In the next step, 910 individuals assigned to full-sib families with more than 28 individuals were subjected to high-resolution genotyping using over one million genome-wide SNPs which were identified with Illumina low-coverage resequencing. Using these SNP genotyping data in principal component analyses we were able to assign individuals to full-sib families with high confidence. Together the analyses revealed five large families with 73–212 individuals. These can be used to generate genetic linkage maps and to perform quantitative trait locus analyses for ash dieback susceptibility. The elucidation of the genetic basis of natural variation in ash may support breeding and conservation efforts and may contribute to more robust forest ecosystems.

A set of nuclear SNP loci derived from single sample double digest RAD and from pool sequencing for large-scale genetic studies in the European beech Fagus sylvatica - Celine Blanc-Jolivet; Malte Mader; Heike Liesebach; Birgit Kersten; Bernd Degen (Conservation Genetics Resources, 2022)
The large-scale spatial genetic structure of European beech, Fagus sylvatica , has been until now poorly studied. We conducted double digest RAD sequencing (ddRADseq) on 54 beech individuals stemming from 36 provenances to discover spatially informative nuclear SNP loci. In addition, two pools derived from 14 early and 14 late flushing individuals each were sequenced with Illumina HiSeq. From an initial amount of 5,464 loci detected by ddRADseq, we selected 559 informative loci. Further 27 additional loci showing significant allelic differences among early and late flushing individuals could be identified after a genotyping on 95 test individuals. The final selection of 578 loci was submitted to probe design for targeted genotyping by sequencing, which yielded 543 loci. The new set of SNP loci should be, after validation on a larger sample size, useful for large-scale genetic studies in this economically-important species.

A novel and diverse set of SNP markers for rangewide genetic studies in Picea abies - Malte Mader; Céline Blanc-Jolivet; Birgit Kersten; Heike Liesebach; Bernd Degen (Conservation Genetics Resources, 2022)
We used Double Digest Restriction site associated DNA sequencing (ddRADseq), exome sequencing (exome-seq) and targeted genotyping by sequencing (GBS) to develop new geographically informative nuclear SNP markers in Picea abies . This set of 518 loci consists of 397 loci specifically designed for the geographic differentiation of populations and 121 loci of adaptive markers for drought stress which all were identified from 26 samples in 23 populations distributed over Central Europe. This set of novel markers represents a valuable basis to study the geographic population structure and genetic differentiation of Picea abies in its natural distribution range as well as outside of its native range with a focus on Central Europe.

Transcriptome analysis of North American sweet birch (Betula lenta) revealed a higher expression of genes involved in the biosynthesis of secondary metabolites than European silver birch (B. pendula) - Kiran Singewar; Birgit Kersten; Christian R. Moschner; Eberhard Hartung; Matthias Fladung (Journal of Plant Research, 2021)
The North American Betula lenta L. (sweet birch) has been used for medicinal reasons for centuries by native Americans. Although sophisticated technologies have rapidly been developed, a large information gap has been observed regarding genetic regulators of medicinally important compounds in sweet birch. Very little is known on the different genes involved in secondary metabolic biosynthesis in sweet birch. To gain a deeper insight into genetic factors, we performed a transcriptome analysis of each three biological samples from different independent trees of sweet and European silver birch ( B. pendula Roth). This allowed us to precisely quantify the transcripts of about 24,000 expressed genes including 29 prominent candidate genes putatively involved in the biosynthesis of secondary metabolites like terpenoids, and aromatic benzoic acids. A total number of 597 genes were differentially expressed between B. lenta and B. pendula , while 264 and 210 genes showed upregulation in the bark and leaf of B. lenta , respectively. Moreover, we identified 39 transcriptional regulatory elements, involved in secondary metabolite biosynthesis, upregulated in B. lenta . Our study demonstrated the potential of RNA sequencing to identify candidate genes interacting in secondary metabolite biosynthesis in sweet birch. The candidate genes identified in this study could be subjected to genetic engineering to functionally characterize them in sweet birch. This knowledge can be beneficial to the increase of therapeutically important compounds.

Development of nuclear SNP markers for Mahogany (Swietenia spp.) - Birte Pakull; Lasse Schindler; Malte Mader; Birgit Kersten; Celine Blanc-Jolivet; Maike Paulini; Maristerra R. Lemes; Sheila E. Ward; Carlos M. Navarro; Stephen Cavers; Alexandre M. Sebbenn; Omar di Dio; et al. (Conservation Genetics Resources, 2020)
Swietenia species are the most valuable American tropical timbers and have been heavily overexploited for decades. The three species are listed as either vulnerable or endangered by IUCN and are included on Appendix II of CITES, yet illegal exploitation continues. Here, we used restriction associated DNA sequencing to develop a new set of 120 SNP markers for Swietenia sp., suitable for MassARRAY®iPLEX™ genotyping. These markers can be used for population genetic studies and timber tracking purposes.

Sequencing of two transgenic early-flowering poplar lines confirmed vector-free single-locus T-DNA integration - Birgit Kersten; Ana Paula Leite Montalvão; Hans Hoenicka; Cristina Vettori; Donatella Paffetti; Matthias Fladung (Transgenic Research, 2020)
Next-generation sequencing (NGS) approaches are attractive alternatives to the PCR-based characterisation of genetically modified plants for safety assessment and labelling since NGS is highly sensitive to the detection of T-DNA inserts as well as vector backbone sequences in transgenic plants. In this study, two independent transgenic male Populus tremula lines, T193-2 and T195-1, both carrying the FLOWERING LOCUS T gene from Arabidopsis thaliana under control of a heat-inducible promoter (pHSP:: AtFT ) and the non-transgenic control clone W52, were further characterised by NGS and third-generation sequencing. The results support previous findings that the T-DNA was hemizygously inserted in one genomic locus of each line. However, the T-DNA insertions consist of conglomerations of one or two T-DNA copies together with a small T-DNA fragment without AtFT parts. Based on NGS data, no additional T-DNA splinters or vector backbone sequences could be identified in the genome of the two transgenic lines. Seedlings derived from crosses between the pHSP:: AtFT transgenic male parents and female wild type plants are therefore expected to be T-DNA splinter or vector backbone free. Thus, PCR analyses amplifying a partial T-DNA fragment with AtFT -specific primers are sufficient to determine whether the seedlings are transgenic or not. An analysis of 72 second generation-seedlings clearly showed that about 50% of them still reveal the presence of the T-DNA, confirming data already published. To prove if unanticipated genomic changes were induced by T-DNA integration, extended future studies using long-range sequencing technologies are required once a suitable chromosome-level P. tremula reference genome sequence is available.

Correction to: Long-term study of a subdioecious Populus ×canescens family reveals sex lability of females and reproduction behaviour of cosexual plants - Maurizio Sabatti; Muriel Gaudet; Niels A. Müller; Birgit Kersten; Cosimo Gaudiano; Giuseppe Scarascia Mugnozza; Matthias Fladung; Isacco Beritognolo (Plant Reproduction, 2020)

Long-term study of a subdioecious Populus ×canescens family reveals sex lability of females and reproduction behaviour of cosexual plants - Maurizio Sabatti; Muriel Gaudet; Niels A. Müller; Birgit Kersten; Cosimo Gaudiano; Giuseppe Scarascia Mugnozza; Matthias Fladung; Isacco Beritognolo (Plant Reproduction, 2020)

Selfing of a single monoecious Populus tremula tree produces viable males, females and “supermales” - Matthias Fladung; Marek Schildbach; Hans Hoenicka; Birgit Kersten; Niels A. Müller (Trees, 2019)

Knockdown of PCBER1, a gene of neolignan biosynthesis, resulted in increased poplar growth - Tobias Bruegmann; Hendrik Wetzel; Kay Hettrich; Annika Smeds; Stefan Willför; Birgit Kersten; Matthias Fladung (Planta, 2019)

Development of nuclear SNP markers for the timber tracking of the African tree species Sapelli, Entandrophragma cylindricum - Céline Blanc-Jolivet; Birgit Kersten; Nils Bourland; Erwan Guichoux; Adline Delcamp; Jean-Louis Doucet; Bernd Degen (Conservation Genetics Resources, 2018)

Genomics of sex determination in dioecious trees and woody plants - Birgit Kersten; Birte Pakull; Matthias Fladung (Trees, 2017)

Development of nuclear, chloroplast and mitochondrial SNP markers for Khaya sp. - Birte Pakull; Malte Mader; Birgit Kersten; Marius R. M. Ekué; Ulrich G. Bouka Dipelet; Maike Paulini; Z. Henri-Noël Bouda; Bernd Degen (Conservation Genetics Resources, 2016)

Development of mitochondrial SNP markers in different Populus species - Birgit Kersten; Mina Merle Voss; Matthias Fladung (Trees, 2015)

Large-scale plant proteomics - Birgit Kersten; Lukas Bürkle; Eckehard J. Kuhn; Patrick Giavalisco; Zoltan Konthur; Angelika Lueking; Gerald Walter; Holger Eickhoff; Ulrich Schneider (Plant Molecular Biology, 2002)